(untitled) (Indian Journal of Animal Production and Management, 2016)
The present study was carried out on 24 growing finishing crossbred (Tamworth x Desi) pigs maintained at All India Coordinated Research Project on Pig (under Mega Seed Project), College of Veterinary Science, Assam Agricultural University, Khanapara, Guwahati, Assam. Six castrated grower pigs of average body weight (25.88 kg) at the end of rearing period (13 weeks of age) were selected from the litters of 5 sows (at least one grower pig per litter) which were weaned at 28 days of age. Similarly, 18 other castrated grower pigs (six per weaning group) were selected from the litters of 15 sows (5 sows in each weaning group) which were weaned at 35, 42 and 56 days of age. The selected pigs were reared individually and reared under farm condition till the end of slaughter age (34 weeks of age). All the experimental animals were fed to the appetite on concentrate rations prepared as per the standards given by NRC (1998). Pigs weaned early (28 or 35 days), having significantly (P<0.05) higher body weight at the beginning of the growing period (week 14) used to grow fast and their superiority in body weight continued till slaughter (at 34 weeks) compared to late (42 or 56 days) weaned pigs. Average daily gain (ADG) taken at 4 weekly intervals were increased up to 21 weeks of age and thereafter it declined for all pigs under different weaning groups and overall ADG during the growing finishing period (end of 13th to 34th weeks) were numerically higher in pigs weaned early. Data of feed conversion efficiency (FCE) of growing-finishing pigs revealed non-significant (P<0.05) difference among the different weaning groups throughout the different periods of growth.